AMRmap: An Interactive Web Platform for Analysis of Antimicrobial Resistance Surveillance Data in Russia - Kuzmenkov, Alexey Y.; Trushin, Ivan V.; Vinogradova, Alina G.; Avramenko, Andrey A.; Sukhorukova, Marina V.; Malhotra-Kumar, Surbhi; Dekhnich, Andrey V.; Edelstein, Mikhail V.; Kozlov, Roman S. (Frontiers in Microbiology, 2021)
Surveillance of antimicrobial resistance (AMR) is crucial for identifying trends in resistance and developing strategies for prevention and treatment of infections. Globally, AMR surveillance systems differ in terms of organizational principles, comprehensiveness, accessibility and usability of data presentation. Until recently, the data on AMR in Russia were scarcely available, especially to international community, despite the fact that the large prospective multicenter surveillance in Russia was conducted and data were accumulated for over 20 years. We describe the source of data, structure and functionality of a new-generation web platform, called AMRmap (https://amrmap.net/), for analysis of AMR surveillance data in Russia. The developed platform currently comprises susceptibility data of >40,000 clinical isolates and the data on abundance of key resistance determinants, including acquired carbapenemases in gram-negatives, and is updated annually with information on >5,000 new isolates. The AMRmap allows smart data filtration by multiple parameters and provides interactive data analysis and visualization tools: MIC and S/I/R distribution plots, time-trends and regression plots, associated resistance plots, prevalence maps, statistical significance graphs and tables.